Evaluation of continuous and intermittent trickling strategies for the removal of hydrogen sulfide in a biotrickling filter. (March 2022) - Bu, Hao; Carvalho, Gilda; Huang, Casey; Sharma, Keshab R.; Yuan, Zhiguo; Song, Yarong; Bond, Philip; Keller, Jurg; Yu, Miao; Jiang, Guangming
Abstract: Biotrickling filter (BTF) is a widely applied bioreactor for odour abatement in sewer networks. The trickling strategy is vital for maintaining a sound operation of BTF. This study employed a lab-scale BTF packed with granular activated carbon at a short empty bed residence time of 6 s and pH 1–2 to evaluate different trickling strategies, i.e., continuous trickling (different velocities) and intermittent trickling (different trickling intervals), in terms of the removal of hydrogen sulfide (H2 S), bed pressure drop, H2 S oxidation products and microbial community. The H2 S removal performance decreased with the trickling velocity (∼3.6 m/h) in BTF. In addition, three intermittent trickling strategies, i.e., 10-min trickling per 24 h, 8 h, and 2 h, were investigated. The H2 S elimination capacity deteriorated after about 2 weeks under both 10-min trickling per 24 h and 8 h. For both intermittent (10-min trickling per 2 h) and continuous trickling, the BTF exhibited nearly 100 % H2 S removal for inlet H2 S concentrations < 100 ppmv, but intermittent BTF showed better removal performance than continuous trickling when inlet H2 S increased to 120–190 ppmv. Furthermore, the bed pressure drops were 333 and 3888 Pa/m for non-trickling and trickling periods, respectively, which makes intermittent BTF save 83 % energy consumption of the blower compared with continuous tirckling. However, intermittent BTF exhibited transient H2 S breakthrough (<1 ppmv) during trickling periods. Moreover, elemental sulfur and sulfate were major products of H2 S oxidation and Acidithiobacillus was the dominant genus in both intermittent and continuous trickling BTF. A mathematical model was calibrated for the intermittent BTF and a sensitivity analysis was performed on the model. It shows mass transfer parameters determine the H2 S removal. Overall, intermittent trickling strategy is promising for improving odour abatement performance and reducing the operating cost of the BTF. Graphical abstract: Image 1 Highlights: A moderate trickling velocity below 1.5 m/h achieves the highest H2 S removal. Both 10-min trickling per 2 h and continuous trickling achieved nearly 100 % H2 S removal. Transient elevation of outlet H2 S occurs during the trickling period of intermittent trickling BTF. Microbial communities are similar for both trickling strategies. Intermittent trickling greatly reduces the energy consumption of the blower due to the lower bed pressure drop.